2021
DOI: 10.53126/mebxxiv001
|View full text |Cite
|
Sign up to set email alerts
|

OctoberFAST: segni e sintomi dei bambini sottoposti a tampone per SARS-CoV-2

Abstract: Background - From the beginning of the SARS-CoV-2 outbreak one major issue has been the early identification of infectious cases. It is particularly challenging to perform a symptom-based screening in the paediatric population because of the seeming overlap of early clinical manifestations between Covid-19 and other common viral infections. Aims - This study was aimed to assess the likelihood that clinical scenarios driving to the SARS-CoV-2 molecular swab test (SMST) might be suggestive for Covid-19 in childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The symptoms described in our study were similar to those reported for school-aged children in a study carried out in an Italian outpatient setting [8]. Our results not only showed a more probable positive test in children presenting fever, but we also found chills, ageusia and headache related to a higher risk of a positive test, while rhinorrhoea, sore throat, and diarrhoea as reduced risks.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…The symptoms described in our study were similar to those reported for school-aged children in a study carried out in an Italian outpatient setting [8]. Our results not only showed a more probable positive test in children presenting fever, but we also found chills, ageusia and headache related to a higher risk of a positive test, while rhinorrhoea, sore throat, and diarrhoea as reduced risks.…”
Section: Plos Onesupporting
confidence: 89%
“…Evidence available on the differential diagnosis between SARS-CoV-2 and coexisting seasonal infections are limited [4]. At present, most of the studies described symptoms in SARS-CoV-2 positive subjects, while a very limited number of studies tried to characterize clinical and epidemiological risk factors able to predict the positivity for SARS-CoV-2 [5][6][7][8][9]. Health care professionals and policy-makers could benefit from knowing which presenting characteristics and symptoms are most likely to be associated with SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%